Analysis of School Disaster Preparedness in Mount Merapi Eruption-Prone Areas: A Case Study in Sleman Regency, Yogyakarta - Krisdiyanto, Didik; Farihah, Tutik (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
Indonesia, situated within the Pacific Ring of Fire, exhibits a unique combination of dynamic tectonic plates and active volcanoes, rendering it susceptible to various seismic activities, ranging from minor tremors to large-scale earthquakes (megathrust). Volcanic eruptions, a prevalent natural disaster in Indonesia, pose significant threats due to the presence of over 130 active volcanoes, with 129 concentrated on Java Island alone. Among these, Mount Merapi stands out as the most active and perilous, situated 30 kilometers north of Yogyakarta City, spanning the administrative boundaries of Yogyakarta Special Region and Central Java. Educational institutions, particularly schools, serve as vital hubs equipped with resources and infrastructure that demand meticulous preparation for potential disasters. This research endeavors to assess the level of school preparedness in the face of disasters, with a specific focus on volcanic eruptions. Through data processing and analysis, it is discerned that Y Primary School in Girikerto village exhibits the highest average preparedness score across five criteria: disaster management plan, community action plan, rehabilitation efforts, early warning system, and competency (89.66%). This is followed by X Primary School (82.39%) and Z Primary School (22.61%). In a broader context, the study reveals that 17.4% of respondents exhibit low preparedness, 4.35% fall within the medium preparedness category, while 34.8% and 43.5% demonstrate high and very high preparedness respectively.